2014
DOI: 10.1007/s11032-014-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping for root architectural traits in durum wheat seedlings as related to agronomic performance

Abstract: Association mapping provides useful insights on the genetic architecture of quantitative traits across a large number of unrelated genotypes, which in turn allows an informed choice of the lines to be crossed for a more accurate characterization of major QTLs in a biparental genetic background. In this study, seedlings of 183 durum wheat elite accessions were evaluated in order to identify QTLs for root system architecture (RSA). The QTLs identified were compared with QTLs detected for grain yield and its comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
117
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 82 publications
(125 reference statements)
21
117
1
1
Order By: Relevance
“…In case of linseed different types of DNA based markers includingAFLP,RAPD,retrotransposon,ISSR,SSRs,SNPetc. havebeenusedforevaluatingthegenetic diversityandlinkage mapping (Cloutier et al 2010;Oh et al 2000;Spielmeyer et al 1998).OverothertypesofDNAmarkers,SSRsarewidelyused forgeneticdiversityandstructureanalysisinseveralcropplants (Cheng et al 2015;Yan et al 2009;Cane et al 2014;Cui et al 2013). In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In case of linseed different types of DNA based markers includingAFLP,RAPD,retrotransposon,ISSR,SSRs,SNPetc. havebeenusedforevaluatingthegenetic diversityandlinkage mapping (Cloutier et al 2010;Oh et al 2000;Spielmeyer et al 1998).OverothertypesofDNAmarkers,SSRsarewidelyused forgeneticdiversityandstructureanalysisinseveralcropplants (Cheng et al 2015;Yan et al 2009;Cane et al 2014;Cui et al 2013). In the present investigation, we applied 50 widely distributed SSRs to evaluate the genetic diversity and identify diverseaccessions/groupofaccessionsamongalargesetof168 accessionsoflinseed.Atotalof337allelesweredetectedfrom50 SSRswithanaverageof6.74allelesperSSRs.Thisaverageallele numberwasfoundtobehigherthanthatreportedearlier (RooseAmsalegetal.2006;Dengetal.2011;Palietal.2014;Soto-Cerda etal.2012Cloutieretal.2012b).Thehigherallelenumber mightbeduetothelargeanddiversesetofaccessionsandwidely distributed SSRs used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main problems of using artificial PGS for characterizing the root phenotype is that root development might not be the same as in the ground. Nevertheless, studies in bean, maize, rice and soybean all indicate a relationship that exists between the results obtained for different RSA characteristics in the field and in artificial systems (Bengough et al 2004;Sanguineti et al 2007;Zhu et al 2011;Canè et al 2014). The present work shows that, for all three species of Brachypodium taken as a whole, the type of PGS (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different authors have reported intergenotypic differences for several characteristics of the root system of rice (Price et al 1997), bread wheat (Waines and Ehdaie 2007) or durum wheat (Sanguineti et al 2007, Canè et al 2014. Pacheco-Villalobos and Hardtke (2012) observed variation in the RSA of different accessions of Brachypodium and Ingram et al (2012) studied two accessions of B. distachyon that showed different RSA behaviour in different nutrient media: while one maintained the growth of auxiliary roots in low N conditions, the other maintained lateral root growth in low P conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although AM has mostly targeted traits with a genetic basis less complex than drought tolerance (e.g. resistance to biotic stress), some studies have targeted drought-adaptative traits and grain yield in durum wheat grown under varying water regimes (Sanguineti et al 2007 ;Maccaferri et al 2011 ;Canè et al 2014 ;Graziani et al 2014 ).…”
Section: Dissecting the Genetic Basis Of Drought Resistance In Durum mentioning
confidence: 99%